2016
DOI: 10.1186/s12968-017-0390-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic utility of differential tissue characterization of cardiac neoplasm and thrombus via late gadolinium enhancement cardiovascular magnetic resonance among patients with advanced systemic cancer

Abstract: BackgroundLate gadolinium enhancement (LGE-) cardiovascular magnetic resonance (CMR) is well-validated for cardiac mass (CMASS) tissue characterization to differentiate neoplasm (CNEO) from thrombus (CTHR): Prognostic implications of CMASS subtypes among systemic cancer patients are unknown.MethodsCMASS + patients and controls (CMASS -) matched for cancer diagnosis and stage underwent a standardized CMR protocol, including LGE-CMR (IR-GRE) for tissue characterization and balanced steady state free precession c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…When performing a CMR study to assess cardiac masses, one can locate determine the etiology and assess the functional importance of the mass on cardiac performance ( 128 , 129 ). Visualizing and comparing the behavior of voxels within the mass with these various imaging techniques allows the differentiation of cardiac tumors from thrombi ( 127 131 ).…”
Section: Additional Cmr Evaluations In Patients With Cancermentioning
confidence: 99%
“…When performing a CMR study to assess cardiac masses, one can locate determine the etiology and assess the functional importance of the mass on cardiac performance ( 128 , 129 ). Visualizing and comparing the behavior of voxels within the mass with these various imaging techniques allows the differentiation of cardiac tumors from thrombi ( 127 131 ).…”
Section: Additional Cmr Evaluations In Patients With Cancermentioning
confidence: 99%
“…[ 19 ] Chan et al clearly stated that late gadolinium enhancement CMR imaging enables cardiac neoplasm to be differentiated from thrombus based on vascular composition. [ 20 ] Mousavi et al found both benign and malignant masses were commonly isointense on T1-weighted imaging, while benign masses were more often hyperintense and malignant masses demonstrated both hyperintense or isointense T2-weighted signals. [ 21 ] Furthermore, first-pass perfusion of the mass was more frequent in malignant than benign tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing level II/III certification in CMR requires CME credit. The first CME offering was for a manuscript by Chan and colleagues on the tissue characterization of cardiac neoplasm and thrombus [ 1 ]. We had 2 offerings in 2017 and hope to have quarterly offerings in 2018.…”
Section: Jcmr Publication/review Processmentioning
confidence: 99%